The Implementation of an Ethical Education Curriculum in Secondary Schools in Ireland - Maria Bourke; William Kinsella; Paula Prendeville (MDPI AG, 2019)
The paper investigates teachers' and principals' experiences of implementing a pilot of an ethical education (EE) curriculum to a senior cycle programme in Educate Together secondary schools in Ireland. The development of this curriculum was informed by the Integrative Ethical Education Model (Lapsley and Narvaez, 2004). Thirteen teachers and two school principals were interviewed about their experiences of this curriculum and its impact on school culture and organisation. An implementation science approach informed a thematic analysis of transcripts that interrogated the perspectives of participants, and revealed the systemic factors that included barriers to, and facilitators of, EE curriculum implementation. Interviews were analysed inductively, by exploring participants' experiences, and deductively, using Narvaez's framework of ethical skills. Results were presented within the domains of school setting, wider school setting, curriculum characteristics and teacher characteristics, reflecting an implementation science approach. Findings suggest that this curriculum nurtured a positive school climate where students identified as having a greater sense of school belonging as a result of access to this curriculum.